The life of Robert Loraine : the stage, the sky, and George Bernard Shaw - Liggera, Lanayre D., 1941- (University of Delaware Press ; The Rowman and Littlefield Publishing Group, Incorporated, 2013)
During his life, Robert Loraine interacted with a number of influential people of surprisingly diverse positions. An adventurer both physically and intellectually, his charismatic personality was recognized on both sides of the Atlantic.